THE INFLUENCE OF UNCERTAINTY, COMMUNICATION AND EMPLOYEE PASSION ON READINESS TO CHANGE AT PT XYZ - Benidiktus Bina Kurniawan; Nidya Dudija (Jurnal Indonesia Sosial Teknologi, 2025)
Organizational change often brings uncertainty among employees, which can affect their readiness to adapt to the change. In this context, effective communication and employee passion are key factors in reducing uncertainty and increasing readiness to change. PT XYZ, a large manufacturing company in Indonesia, is undergoing a digital transformation through the implementation of a new ERP system aimed at improving work efficiency and effectiveness. This study aims to explore the influence of uncertainty, communication, and passion on employee readiness to change at PT XYZ. The objective of this study is to examine the influence of uncertainty, communication, and employee passion on readiness to change at PT XYZ. This study also aims to identify the most significant factors affecting employee readiness to adapt to the ongoing changes. Thus, it is expected that this research will provide valuable insights for PT XYZ's management in managing change and minimizing employee resistance. Using a quantitative approach, data were collected from 266 employees across various departments and analyzed with the Partial Least Squares (PLS) method. The findings reveal that uncertainty negatively affects readiness to change, while effective communication and employee passion significantly enhance it. Notably, communication effectiveness and employees’ enthusiasm for change emerged as key drivers of organizational adaptability. The study highlights the need for PT XYZ’s management to minimize uncertainty through transparent communication strategies and foster a positive work culture to enhance employee readiness. These insights provide valuable guidance for organizations undergoing similar transformations, emphasizing the critical role of communication and employee engagement in change management success.